ANALISIS SEMIOTIKA PADA PUISI “DALAM DOA: II” KARYA SAPARDI DJOKO DAMONO - Nuraeni Agustina; Rochmat Tri Sudradjat; Heri Isnaini (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This article analyzes the signs found in the poem "Dalam Doa: II" by Sapardi Djoko Damono. The focus of this research is as follows. 1) what are the signs in Sapardi Djoko Damono's poem "Dalam Doa: II"?; and 2) how is the meaning built on the poem "Dalam Doa: II" based on the signs found?. This study uses the theory of semiotics put forward by Carles Sanders Pierce by analyzing the signs on poetry. The mark analysis used refers to the relationship of a mark to an object, i.e. a mark that is an icon, an index, and a symbol. The signs found will eventually refer to the meaning and understanding of the poem in its entirety. The results of this study showed that the signs contained in the poem "Dalam Doa: II" by Sapardi Djoko Damono consists of signs in the form of symbols, namely symbols that can build meaning about the values of religiosity in poetry. Thus, the use of semiotics theory in analyzing the poem "Dalam Doa: II" by Sapardi Djoko Damono has an important role in understanding and interpreting poetry as a whole